Wind Turbine Electrical Energy Supply System for Oil Well Heating - A. A. Belsky; V. A. Morenov; K. S. Kupavykh; M. S. Sandyga (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
In this article, the authors reviewed a new technology to prevent the formation of asphalt-resin-paraffin deposits by the thermal method of electrothermal impact on the oil wellbore shaft using a wind-electric installation as an autonomous power source. The advantage of this thermal stimulation technique lies in its continuous nature, which will allow keeping the clear opening of the tubing constant. The scheme of the autonomous system for down-hole electric heating of oil is presented. A tubular or induction heater can serve as an electric heating element placed in the well. The heating element of the system can be used in the wells exploited by freeflow, gas lift and mechanized methods, while its installation does not require an overhaul. The paraffin oil saturation temperature and temperature distribution over the depth of the well were defined. The amount of heat, which must be transferred to the oil mixture in the tubing in order to ensure effective operation of the well, taking into account the dynamic state of the system, is calculated. The optimal depth of the heating element's location in the well and its power was determined. The calculation of the required power for wind-electric installation to maintain the set temperature in the wellbore was performed. Having conducted the studies, it was revealed that in order to prevent the asphalt-resin-paraffin deposits formation on the tubing walls of oil wells, it is expedient to use the in-line heater, which maintains the average steady-state temperature along the wellbore and at the wellhead above the initial crystallization point of the asphaltresin-paraffin deposits. The application of the developed electrothermal system is relevant in the conditions of formation of asphalt-resin-paraffin deposits in the wellbore shaft at the fields, which do not have a connection to the centralized power grid.